2015
DOI: 10.1108/jcp-12-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender, rape myth acceptance, and perpetrator occupation on perceptions of rape

Abstract: Purpose – The purpose of this paper is to assess the impact of gender-stereotypical beliefs and associated factors (gender, level of rape myth acceptance (RMA), and occupation) on public attitudes towards rape victims with the aim of establishing whether participant and perpetrator characteristics have effects on individuals’ attitudes towards rape victims. With regards to participants, gender, age, occupation, and the extent to which an individual endorses rape myths were investigated. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
7
0
3
Order By: Relevance
“…A meta-analysis of 37 studies conducted by Suarez and Gadalla (2010) found a marked gender gap in rape myth acceptance, with men routinely showing higher acceptance compared to women, and confirmed that measures of sexism and hostility toward women were significant predictors of rape myth acceptance (see also Aosved & Long, 2006;Chapleau et al, 2008;Ståhl, Eek, & Kazemi, 2010). Rape myth acceptance is associated with a higher proclivity to rape (Chiroro, Bohner, Viki, & Jarvis, 2004), how people perceive rape and assign blame (Basow & Minieri, 2011; see also Chapleau & Oswald, 2013;Duff & Tostevin, 2015) can prevent women from defining unwanted sexual encounters as rape (Peterson & Muehlenhard, 2004; see also Eyssel & Bohner, 2011;Heath, Lynch, Fritch, & Wong, 2013;Lemaire, Oswald, & Russell, 2016) and make bystanders less likely to intervene in potentially threatening situations (McMahon, 2010).…”
Section: Previous Researchmentioning
confidence: 76%
“…A meta-analysis of 37 studies conducted by Suarez and Gadalla (2010) found a marked gender gap in rape myth acceptance, with men routinely showing higher acceptance compared to women, and confirmed that measures of sexism and hostility toward women were significant predictors of rape myth acceptance (see also Aosved & Long, 2006;Chapleau et al, 2008;Ståhl, Eek, & Kazemi, 2010). Rape myth acceptance is associated with a higher proclivity to rape (Chiroro, Bohner, Viki, & Jarvis, 2004), how people perceive rape and assign blame (Basow & Minieri, 2011; see also Chapleau & Oswald, 2013;Duff & Tostevin, 2015) can prevent women from defining unwanted sexual encounters as rape (Peterson & Muehlenhard, 2004; see also Eyssel & Bohner, 2011;Heath, Lynch, Fritch, & Wong, 2013;Lemaire, Oswald, & Russell, 2016) and make bystanders less likely to intervene in potentially threatening situations (McMahon, 2010).…”
Section: Previous Researchmentioning
confidence: 76%
“…Studies have consistently found relations between social ideologies and constructs such as sexism and rape myth beliefs. As highlighted by Edwards and colleagues (2011), rape ideologies stem from a patriarchal structure, and attitudes towards rape are more tied to the observer’s belief system, often heavily influenced by one’s cultural norms, than to the victim’s features (Duff & Tostevin, 2015; Kaplan & Miller, 1978).…”
Section: Ideology and Religionmentioning
confidence: 99%
“…Despite the importance of the research about contextual factors, less attention has been paid to characteristics of the aggressor (Anderson et al, 1997). Among other variables, the aggressor's attire (Yarmey, 1985), physical attractiveness (Vrij & Firmin, 2001), social status (Deitz & Byrnes, 1981;Duff & Tostevin, 2015;Yamawaki, Darby, & Queiroz, 2007), and cultural similarity between perceivers and aggressor (Bongiorno, McKimmie, & Masser, 2016) have been considered. In the study by Deitz and Byrnes (1981), perpetrators who were attractive and in higher status occupation were attributed less responsibility for the rape compared with those who were attractive but in lower status occupation.…”
Section: Variables Of the Context: The Role Of The Social Class Of The Aggressormentioning
confidence: 99%